Effects of Smoking on Alveolar Bone Loss of Dental Undergraduate Students in University of Malaya - Fouad Hussain Al-Bayaty; Noor Adinar; Saridah Mahda; Evyline Chin Oi Lian (Faculty of Dentistry, Universitas Indonesia, 2015)
Purpose of the study: This study is undertaken to investigate the prevalence of smoking among dental undergraduate students in the University of Malaya, and to study the effects of smoking on the interproximal bone height. Materials and method: A smoking habits questionnaire was distributed to the 299 dental undergraduate students of Year 2 to Year 5. Students were divided into groups of smokers (history of smoking for at least 1 year), former smokers (history of smoking and stopped more than 1 year) and non-smokers (no smoking history). Two bitewing radiographs (left and right) were taken from 14 smokers and 5 former smokers. In addition, 14 students were randomly picked as control group, and their previously taken bitewing radiographs were collected. Interproximal bone loss defined as the distance (mm) from CEJ to the alveolar crest (AC) was measured using caliper, magnifier and metal ruler. Results: The prevalence of smokers and former smokers among dental students was 5.57% and 1.99% respectively. Mean  SEM of the CEJ-AC distance for smokers and non-smokers was 1.063  0.066 mm and 0.849  0.050 mm, respectively. The difference was statistically significant between the smokers and non-smokers (p<0.05). Mean SEM of bone loss among the smoker was 0.204  0.066 mm. There was no statistically significant difference between former smokers and non-smokers (p>0.05). Premolar is the most affected tooth in smokers, with a mean SEM of the CEJ-AC distance of 1.350  0.102 mm. Conclusions: Smoking prevalence among dental undergraduate students was very low. Smokers have more bone destruction than the non-smokers.